STUDI PEMBUNGAAN TANAMAN MANGGA (Mangifera indica L) DENGAN APLIKASI FACLOBUTRAZOL DAN KNO3 - Ridho, Cholid (MAPETA, 2000)
The purpose of this research was to know the interaction of aplicalion paclobutrazol and KN03 of flower growth mango there search was carried out at wonokerto in Probolinggo district. There search was done in Agustus1999, Applying split plot design. Result indicated that no interaction between application paclobutrazol and KN03. Treatment KN03 of four week after aplication Paclobutrazol (K2) influence on appear flower time and number of flower.